THE EFFECTIVENESS OF HELLO ENGLISH APPLICATION TO TEACH VOCABULARY - Wahyudi, Slamet Agung; Muchyidin, M. Syaichul; Asyhar, Wildan Isna (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
The purpose of this research is to know the effect of Hello English application on student’s vocabulary achievement in XI grade students of SMAN 2 pare. Using the correct instructional media and approaches can assist students in mastering English vocabulary. Researchers are interested in studying the possibilities of the Hello English application being reviewed as an effective learning media. To design this research, quantitative research technique was used to design this research. The experimental group was taught with Hello English application, whereas the control group was not. As data collecting methods, pretest and posttest were used. The results indicated a considerable difference between the classes that used application and the other ones. This is evidenced by the disparity in average scores. The average pre-test score for the experimental class was 71.50 and the control group was average score 70.33 and post-test 84.50 in experimental class while in control class 79.67. In addition, the use of independent t-test findings was determined to be 0.004. That is less than 0.05. It can be concluded that teaching vocabulary using Hello English application is effective.